(untitled) (International Educators Conference, 2025)
The article discusses plant height and lodging resistance parameters in varietal samples obtained from the Central Asian and Kyrgyz soft wheat germplasm, which possess broad genetic diversity, under the conditions of meadow alluvial soils of the Khorezm region.